2005 IEEE Engineering in Medicine and Biology 27th Annual Conference 2005
DOI: 10.1109/iembs.2005.1616587
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Wearable Device Capable of Monitoring Human Activity for Use in Rehabilitation and Certification of Eligibility for Long-Term Care

Abstract: The importance of human posture monitoring is well recognized in the field of rehabilitation, in order to evaluate quantitatively the effectiveness of rehabilitation by a physical therapist. The activity monitoring is also well recognized as being useful in the field of certification of eligibility for long-term care. Assessment of the actual physical condition of the applicant tends to be difficult when determine the level of need for long-term care. Taking these circumstances in consideration, we attempted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…The now 16 studies [ 31 - 46 ] were categorized according to whether they proposed ABT-methods ( N = 11), evaluated ABT-outcome measures ( N = 6) able to assess mobility characteristics of functional activities, or performed a combination of both. A total of 12 studies passed the validation screening and were finalized for this review: nine method studies [ 31 - 34 , 38 , 39 , 42 , 43 , 45 ], four outcome studies [ 33 , 37 , 40 , 44 ], in which one study [ 33 ] straddles both categories. A total overview of included studies can be found in Additional file 2 : Appendix B and Additional file 3 : Appendix C.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The now 16 studies [ 31 - 46 ] were categorized according to whether they proposed ABT-methods ( N = 11), evaluated ABT-outcome measures ( N = 6) able to assess mobility characteristics of functional activities, or performed a combination of both. A total of 12 studies passed the validation screening and were finalized for this review: nine method studies [ 31 - 34 , 38 , 39 , 42 , 43 , 45 ], four outcome studies [ 33 , 37 , 40 , 44 ], in which one study [ 33 ] straddles both categories. A total overview of included studies can be found in Additional file 2 : Appendix B and Additional file 3 : Appendix C.…”
Section: Resultsmentioning
confidence: 99%
“…Studies evaluating ABT-methods were mainly PD studies ( n = 6) [ 31 , 32 , 38 , 42 , 43 , 45 ] and, to a lesser extent, stroke ( n = 3) [ 33 , 34 , 39 ]. None involved other neurological conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further research on these interventions is needed. Recent literature presents systems used for long acquisitions of gait measurement [ 36 , 37 , 38 ]. Using these systems, in addition to being able to measure a more natural gait, it will be possible to obtain a well gait by giving feedback when patients walk with appropriate joint angle.…”
Section: Discussionmentioning
confidence: 99%